Training for Women's Groups on Papaya Production Management in Papaya Jam in Sambirejo - Leni Vitasari; M. Iswahyudi; Mahfud (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
Papaya is one of the superior products occupied by farmers in Sambirejo Village, Bangorejo District, Banyuwangi Regency, taking into account the economic potential of the harvest obtained. The main problem that arises is that harvests cannot be carried out simultaneously, resulting in inefficiency in the distribution process of harvested crops outside the region. On the other hand, the harvest exceeds the consumption demand of the local community so that there is a decrease in the value of the product used as animal feed. Against this problem, it is necessary to innovate processing papaya products into various kinds of economic products as well as an effort to empower the community's economy. This effort is part of an out-of-school education program to provide knowledge and skills, namely through innovative training. This training resulted in the innovation of solid papaya soap, liquid hand washing soap and body scrub made from papaya.